Impact of X-rays on CO emission from high-z galaxies. Issue 4 (10th October 2019) - Vallini, L; Tielens, A G G M; Pallottini, A; Gallerani, S; Gruppioni, C; Carniani, S; Pozzi, F; Talia, M
ABSTRACT: We study the impact of active galactic nuclei (AGNs) on the CO spectral line energy distribution (SLED) of high- z galaxies. In particular, we want to assess if the CO SLED can be used as a probe of AGN activity. To this purpose, we develop a semi-analytical model that takes into account the radiative transfer and the clumpy structure of giant molecular clouds where the CO lines are excited, their distribution in the galaxy disc, and the torus obscuration of the AGN radiation. We study the joint effect on the CO SLED excitation of (i) the X-ray luminosity from the AGNs ( L X ), (ii) the size of the molecular disc, (iii) the inclination angle (Ω) of the torus with respect to the molecular disc, and (iv) the Giant Molecular Cloud (GMC) mean density. We also discuss the possibility of an enhanced cosmic ray ionization rate (CRIR). We find that the X-ray-dominated region (XDR) generated by the AGNs in every case enhances the CO SLED for J > 5, with increasing excitation of high- J CO lines for increasing X-ray luminosity. Because high- z galaxies are compact, the XDR typically encloses the whole disc, thus its effect can be more important with respect to lower redshift objects. The impact of the XDR can be disentangled from an enhanced CRIR either if L_ X 10^44 erg s^-1, or if Ω ≥ 60°. We finally provide predictions on the CO(7–6)/[C ii ] and CO(17–16)/[C ii ] ratios as a function of L X, which can be relevant for ALMA follow-up of galaxies and quasars previously detected in [C ii ].